Angiomatosis of the Orbit: Clinical, Imaging, and Histologic Findings. Issue 2 (March 2018) - Vahdani, Kaveh; Kim, Yoon-Duck; Suh, Yeon-Lim; Kim, Jeong Hee
Abstract : Angiomatosis is a complex vascular malformation that denotes a clinically extensive hemangioma, which either involves multiple tissue planes or extensively infiltrates 1 type of tissue. It is a rare condition characterized by diffuse proliferation of blood vessels admixed with fat and fibrotic tissue. Typically, this process involves the limbs in multiple tissue planes, including dermis, subcutis, muscle, and bone. In this report, the authors present the first case of angiomatosis infiltrating the orbit, controlled effectively with a combination of systemic steroids, radiation, and beta-blocker therapy. The characteristic imaging and histologic features and management options are discussed. Abstract : The authors describe a rare case of angiomatosis infiltrating the orbital structures and discuss diagnostic features as well as management challenges.